2002
DOI: 10.1007/s00018-002-8439-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 polyunsaturated fatty acids and coronary heart disease-related mortality: a possible mechanism of action

Abstract: Epidemiological and interventional studies indicate that dietary n-3 PUFA reduces mortality due to coronary heart disease (CHD). They act at a low dose, since one or two meals with fatty fish per week is sufficient to provide protection when compared with no fish intake. These fatty acids are effective in providing primary prevention in low- and high-risk subjects and secondary prevention. At high doses, dietary n-3 PUFAs have several beneficial properties. First, they act favourably on blood characteristics: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 214 publications
1
63
0
1
Order By: Relevance
“…Similar outcomes were found in a prospective cohort study, the PhysiciansÊŒ Health Study, whereby dietary fish intake was associated with a reduced risk of sudden death (252%, P 5 0.03). Known biological activities of n-3 PUFAs important in atherosclerosis include cholesterol lowering (usually minor in humans), triglyceride lowering (good at higher doses), decreased platelet aggregation, reduced blood viscosity, favorable decreases in eicosanoid production responsible for vasodilator and antithrombotic properties, and anti-inflammatory effects (33).…”
Section: Reduction Of Oleate Enrichment In Plasmamentioning
confidence: 99%
“…Similar outcomes were found in a prospective cohort study, the PhysiciansÊŒ Health Study, whereby dietary fish intake was associated with a reduced risk of sudden death (252%, P 5 0.03). Known biological activities of n-3 PUFAs important in atherosclerosis include cholesterol lowering (usually minor in humans), triglyceride lowering (good at higher doses), decreased platelet aggregation, reduced blood viscosity, favorable decreases in eicosanoid production responsible for vasodilator and antithrombotic properties, and anti-inflammatory effects (33).…”
Section: Reduction Of Oleate Enrichment In Plasmamentioning
confidence: 99%
“…In contrast to SFA, unsaturated fatty acids are recognised as health beneficial. A number of studies demonstrated hypo-cholesterolemic effects of monounsaturated fatty acids (MUFAs) and some polyunsaturated fatty acids (PUFAs) (Demaison and Moreau, 2002). MUFA have also been reported to possess anti-thrombogenic properties (Smith et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In some acute clinical situations such as myocardial infarction, it may be advantageous to rapidly modify the n-3 PUFA content in cardiac cell phospholipids; this may not be achieved by oral supplementation with fish oil which generally leads to a significant enrichment after 2 weeks (10). In a recent study on a limited number of patients, Schrepf et al have shown that intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%